A CRISPR/Cas9 zebrafish lamin A/C mutant model of muscular laminopathy. Issue 4 (18th October 2021) - Nicolas, Hannah A.; Hua, Khang; Quigley, Hailey; Ivare, Joshua; Tesson, Frédérique; Akimenko, Marie‐Andrée
Abstract: Background: Lamin A/C gene ( LMNA ) mutations frequently cause cardiac and/or skeletal muscle diseases called striated muscle laminopathies. We created a zebrafish muscular laminopathy model using CRISPR/Cas9 technology to target the zebrafish lmna gene. Results: Heterozygous and homozygous lmna mutants present skeletal muscle damage at 1 day post‐fertilization (dpf), and mobility impairment at 4 to 7 dpf. Cardiac structure and function analyses between 1 and 7 dpf show mild and transient defects in the lmna mutants compared to wild type (WT). Quantitative RT‐PCR analysis of genes implicated in striated muscle laminopathies show a decrease in jun and nfκb2 expression in 7 dpf homozygous lmna mutants compared to WT. Homozygous lmna mutants have a 1.26‐fold protein increase in activated Erk 1/2, kinases associated with striated muscle laminopathies, compared to WT at 7 dpf. Activated Protein Kinase C alpha (Pkc α), a kinase that interacts with lamin A/C and Erk 1/2, is also upregulated in 7 dpf homozygous lmna mutants compared to WT. Conclusions: This study presents an animal model of skeletal muscle laminopathy where heterozygous and homozygous lmna mutants exhibit prominent skeletal muscle abnormalities during the first week of development. Furthermore, this is the first animal model that potentially implicates Pkc α in muscular laminopathies. Key Findings: This study presents an animal model of skeletal muscle laminopathy where heterozygous and homozygous lmna mutants exhibit prominent skeletal muscle abnormalities during the first week of development. The heterozygous and homozygous lmna mutants displayed mild and transient cardiac defects during the first week of development. This is the first animal model that potentially implicates Pkc α in muscular laminopathies.